Australian Aboriginal English change and continuity in an adopted language - Malcolm, Ian G. (Dialects of English,, 2018)
"This is the first volume to provide a comprehensive description of the Aboriginal English dialect with attention to its regional and social variation, the circumstances of its development, its relationships to other varieties and its foundations in the history, conceptual predispositions and speech use conventions of its speakers. The volume includes a review of recent research as well as a bibliography and a number of sample texts"--